Wiki for co-writing a science dictionary - Chong, Moi Lian; Tan, Bee Hoon; Abdullah, Mardziah Hayati (Penerbit Universiti Kebangsaan Malaysia, 2011)
Web technology is known to make learning more engaging, and language educators have been encouraged to use web tools for instruction. This paper discusses the application of Wiki in fostering collaborative writing in a specific upper secondary class. The study investigates how a group of secondary students learned to use Wiki to co-write a science dictionary, and the effects of Wiki on their collaborative efforts in producing the dictionary. The study employed a single-case observation research design. The single case was a class of 23 Form Four students with only 13 students regularly participating in the Wiki project for three months. The participants' perceptions of Wiki were analysed through interviews and a survey questionnaire. Their behaviours were observed while they were in the process of using Wiki in constructing the science dictionary. Results show that students who actively participated in the project perceived Wiki positively, while those who were apprehensive in writing and contributed the least to the project thought otherwise. Active students who were weak in both ICT skills and English had the most to gain because they improved in both areas by the end of the project. A tangible outcome of the collaborative writing project was that by the end of the third month, a Wiki science dictionary was successfully created online at the Tiki-Wiki website. The findings are useful in offering an alternative approach of teaching English as opposed to conventional methods.